Final anatomic and visual outcomes appear independent of duration of silicone oil intraocular tamponade in complex retinal detachment surgery - Maedbh Rhatigan; Elizabeth McElnea; Patrick Murtagh; Kirk Stephenson; Elaine Harris; Paul Connell; David Keegan (International Journal of Ophthalmology, 2018)
AIM: To report anatomic and visual outcomes following silicone oil removal in a cohort of patients with complex retinal detachment, to determine association between duration of tamponade and outcomes and to compare patients with oil removed and those with oil in situ in terms of demographic, surgical and visual factors. METHODS: We reported a four years retrospective case series of 143 patients with complex retinal detachments who underwent intraocular silicone oil tamponade. Analysis between anatomic and visual outcomes, baseline demographics, duration of tamponade and number of surgical procedures were carried out using Fisher’s exact test and unpaired two-tailed t-test. RESULTS: One hundred and six patients (76.2%) had undergone silicone oil removal at the time of review with 96 patients (90.6%) showing retinal reattachment following oil removal. Duration of tamponade was not associated with final reattachment rate or with a deterioration in best corrected visual acuity (BCVA). Patients with oil removed had a significantly better baseline and final BCVA compared to those under oil tamponade (P=0.0001, <0.0001 respectively). CONCLUSION: Anatomic and visual outcomes in this cohort are in keeping with those reported in the literature. Favorable outcomes were seen with oil removal but duration of oil tamponade does not affect final attachment rate with modern surgical techniques and should be managed on a case by case basis.